2023
DOI: 10.3389/fpls.2023.1082761
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters linked to multiple herbicide resistance in blackgrass (Alopecurus myosuroides)

Abstract: Enhanced detoxification is a prominent mechanism protecting plants from toxic xenobiotics and endows resistance to diverse herbicide chemistries in grass weeds such as blackgrass (Alopecurus myosuroides). The roles of enzyme families which impart enhanced metabolic resistance (EMR) to herbicides through hydroxylation (phase 1 metabolism) and/or conjugation with glutathione or sugars (phase 2) have been well established. However, the functional importance of herbicide metabolite compartmentalisation into the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…According to recent study, ABC transporters played an important role in translocating metabolites across membranes through ATP hydrolysis and were additionally involved in the compartmentation and detoxification of herbicides in Alopecurus myosuroides Huds. as confirmed by transcriptomic analysis (Goldberg-Cavalleri et al, 2023).…”
Section: Vacuolar Sequestrationmentioning
confidence: 55%
See 1 more Smart Citation
“…According to recent study, ABC transporters played an important role in translocating metabolites across membranes through ATP hydrolysis and were additionally involved in the compartmentation and detoxification of herbicides in Alopecurus myosuroides Huds. as confirmed by transcriptomic analysis (Goldberg-Cavalleri et al, 2023).…”
Section: Vacuolar Sequestrationmentioning
confidence: 55%
“…Rather, efforts were made to summarize the wide array of resistance mechanisms. Most of the NTSR mechanisms are not fully understood (Baucom, 2019, Goldberg-Cavalleri et al, 2023, however, this review will provide an account of what is known about these mechanisms. The review further discusses how various herbicide resistance management strategies delay resistance evolution, with emphasis on NTSR.…”
Section: Introductionmentioning
confidence: 99%
“…These GSTs from monocot species were selected based on their activity toward herbicides. Sequences were aligned and trimmed as described previously ( Goldberg-Cavalleri et al., 2023 ). Automatic model selection mode was employed (Bayesian information Criterion selecting the model LG+G4+I+F), with branch support values calculated by Ultrafast bootstrap approximation.…”
Section: Methodsmentioning
confidence: 99%
“…Herbicides have been used to control weeds and increase the quality and quantity of major crops since their discovery. However, repeated use of similar herbicidal modes of action (MOAs) and the associated selection pressure have led to the evolution of herbicide resistance in varieties of economically important weedy species such as Alopecurus myosuroides ( Lan et al., 2022 ; Goldberg-Cavalleri et al., 2023 ), Amaranthus palmeri ( Manicardi et al., 2023 ), Apera spica venti ( Košnarová et al., 2021 ; Papapanagiotou et al., 2022 ), Bromus sterilis ( Sen et al., 2021 ), Lolium spp ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Zhu et al., 2023 ). Recent studies showed that the majority of these weeds were also developing multiple resistances against herbicides with more than one mode of action ( Tehranchian et al., 2019 ; Ma et al., 2020 ; Košnarová et al., 2021 ; Lan et al., 2022 ; Papapanagiotou et al., 2022 ; Zhu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%